Impact of the Variable Killer Ig-Like Receptor–Human Leukocyte Antigen Interactions on Natural Killer Cell Cytotoxicity Toward Foreign CD4 T Cells - Hens, Jef; Goovaerts, Odin; Ceulemans, Ann; Jennes, Wim; Kestens, Luc (Frontiers in Immunology, 2018)
Background: Natural killer (NK) cells are known to mount a response against foreign target cells, where the absence of the dominant inhibitory killer Ig-like receptor (KIR) – human leukocyte antigen (HLA) interaction immensely lowers the threshold for NK cell activation. NK cells could thus constitute a vital part in the mucosal defense against cell-associated sexually transmitted diseases. Here, we performed a detailed analysis of hitherto unexplored KIR-HLA incompatible NK cell interactions. Methods and Findings: In vitro, healthy NK cells were co-cultured with CD4+ T cells derived from HIV patients and measured the KIR-specific NK cell cytotoxicity using flow cytometry. Genotyping of KIR and HLA predicted the KIR-HLA interactions occurring during these 124 allogeneic encounters. KIR2DL1+ NK cells were seen as strongest intrinsic responders in the absence of their ligand with a 3,2-fold increase of KIR2DL1+ NK cells in the total NK cell response. An association between the size of the alloreactive NK cell population and the amount of CD4+ T cell death (p=0.0023) and NK cell degranulation (p=0.0036) was only present in NK cell donors with an activating KIR haplotype. Conclusion: We demonstrate differences in the activating effect of KIR-HLA incompatibility according to the KIR involved, with KIR2DL1 as strongest responder. An activating KIR haplotype optimized the contribution of KIR-HLA incompatible NK cells in the total NK cell response.